Evaluating the impact of a digitally implemented subjective standard on professional rugby union player management decision-making - Ranaweera, J.; Weaving, D.; Zanin, M.; Roe, G. (International Journal of Sports Science & Coaching, 2024)
Using a pre-post-test design, this study evaluated the impact of implementing a standard on the reliability of player management decision-making within a professional rugby union environment. Five practitioners from a High-Performance Unit (HPU) rated 22 instances of Global Positioning System (GPS)-based external training load information of 14 players across the 2021-2022 season. This rating was whether a peak/trough/normal exposure in load had occurred. The ratings were repeated at four time points (separated by 2 weeks) before (Pre_1, Pre_2) and after (Post_1, Post_2) implementing a consensus statement as a subjective standard (using a dashboard) developed previously within the same environment to identify peaks/troughs in player external training loads. Inter-rater agreement between individuals at each voting round was assessed using Light's Kappa, while pre-post-standard intra-rater agreement was determined from Cohen's Kappa (both with 95% confidence intervals). Changes to dashboard usability from implementing the standard were assessed by administering the System Usability Scale to 11 HPU staff at the four time points. Pre-standard moderate inter-rater agreement (Pre_1: 0.53 (0.36-0.69), Pre_2: 0.60 (0.42-0.77)) increased to almost perfect agreement (Post_1: 0.74 (0.57-0.89), Post2: 0.90 (0.79-1)) post-standard. The intra-rater agreement of 2/5 participants was almost perfect post-standard, while it remained within substantial levels for the others. A linear mixed model (X^2(3) = 8.85, p = 0.03) illustrated a slight increase in dashboard usability after incorporating the standard (Pre1: 84.09, Pre_2: 81.36; Post_1: 87.73, Post_2: 87.27). Overall, the results highlighted that the subjective standard enhanced reliability of practitioner agreement for the selected decision.